Pengaruh pembelajaran kewirausahaan dan projek kewirausahaan terhadap minat berwirausaha siswa SMK - Afifah, Siti Nur; Saino, Saino (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2025)
This study aims to determine the effect of entrepreneurship learning and entrepreneurship projects on the entrepreneurial interest of students at SMKS YPID. The approach used is quantitative. The population of this study consists of SMKS YPID Class XII students, with a total sample of 79 respondents. The data collection technique used a Likert scale-based questionnaire distributed via Google Forms. The results showed that entrepreneurship learning has a positive but insignificant effect on student entrepreneurship interest. In contrast, entrepreneurship projects have a positive and significant effect on student entrepreneurship interest. Furthermore, the combined impact of entrepreneurship learning and entrepreneurship projects on students' interest in entrepreneurship is also positive and essential. Based on these results, the most influential variable on student entrepreneurial interest in this study is the entrepreneurship project.